On the role of future high-frequency BFWA systems in broadband communication networks. - Tardy, Isabelle (IEEE Communications magazine)
Frequencies above 25 GHz represent a great opportunity for BFWA systems because of the extraordinary bandwidths available. But standards for high-frequency BFWA published so far have not been able to unleash this potential. We believe this is due to the fact that the performance characteristics have been shaped considering these systems in isolation. This has brought on a mismatch between what these systems can offer and what is really needed. Most of today's broadband networks focus on data communication. In this article, we focus on how to make high-frequency BFWA systems fit better into the architecture required for fulfilling the "broadband for all" vision (i.e., including more video streaming and transfer). By modifying and extending the standards to fulfill the performance requirements implied, high-frequency BFWA systems can play an important role in future high-capacity broadband networks with flexible resource allocation.